Branching Pattern of Portal Vein in Pig Liver - Kirpal Singh; Varinder Uppal; Neelam Bansal; Anuradha Gupta; Devendra Pathak (Indian Journal of Veterinary Anatomy, 2026)
The study was conducted on three pig livers collected from local slaughter house. Normal saline wasinjected to flush the portal vein. For cast preparation, 10 g of orthoplast powder and 20 ml of cross-linkedorthoplast denture material was mixed. The blue colour was imparted by adding asian blue paint. The solution wasstirred to attain honey like consistency. The blue solution was injected in portal vein. Then the organ was allowedto set for 4-6 hours and then transferred to conc. HCL. As tissue was dissolved in HCL, the cast was removed andwashed with water. The study revealed the ramification of portal vein within the parenchyma of liver.